Pengaruh Bauran Promosi Terhadap Volume Penjualan Pada Mobil Daihatsu Grand Max Di Daihatsu Sales Point Kota Metro - Faturrachman, Muhammad Arief; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2022)
Basically the goal in establishing a company is how they look for consumers as much as possible to increase sales volume, while the sales volume is the final result achieved by the company from the sale of products made by the company. For this reason, the sales volume is calculated based on the assumed target with the realization achieved. The purpose of this study is to determine whether there is an influence of advertising costs, the cost of sales promotion and personal sales of sales volume on Daihatsu Grand Max cars at Daihatsu Metro City Sales Points. This research method is descriptive qualitative, which produces descriptive data based on the results of quantitative analysis with company secondary file on research variables. File collection techniques using corporate secondary data, documentation and literature study. The analytical tool used is multiple linear regression. The results are obtained when the results of testing together that the three independent variables including advertising costs, sales promotion, and personal sales have a positive and significant effect on sales volume.